STUDY REGARDING THE ASSOCIATION BETWEEN CHRONIC PERIODONTITIS AND THE PREVALENCE OF HEAD-NECK CARCINOMA - Diana-Cristala Nițescu; Cristian Mârţu; Sorina Solomon; Irina Ursărescu; Ioana Mârțu; Lucian Burlea; Silvia Mârțu1 (Romanian Society of Oral Rehabilitation, 2015)
Background and aim Substantial evidence supports an association between chronic infections/inflammation, and cancer. The aim of this study was to assess the effect of chronic periodontitis on head and neck squamouscell carcinoma (HNSCC). Material and methods The study population consisted of 46 patients, divided into two groups. Cases were patients diagnosed with primary HNSCC (n=26). Controls were all patients seen during the same period of time but negative for malignancy (n=20). The severity of periodontitis was assessed through clinical determination of the bleeding index, periodontal index, tooth mobility degree and alveolar bone loss (ABL) on standardized panoramic radiographs. Results and discussions: Each millimeter of ABL was associated with >4-fold increased risk of HNSCC. The strength of the association was greatest in the oral cavity, followed by the oropharynx and larynx. The association persisted in subjects who never used tobacco and alcohol. Patients with periodontitis, whose bleeding and periodontal indices and tooth mobility values were higher, were more likely to have poorly differentiated oral cavity SCC than those without periodontitis (32.8% versus 11.5%; P = 0.038). Conclusions This study suggests that chronic periodontitis is a risk factor for HNSCC. These results have implications for practical and improved strategies for prevention, diagnosis, and treatment of HNSCC.